OPTIMIZATION OF CR(VI) BIOTRANSFORMATION BY RESPONSE SURFACE METHODOLOGY USING MICROBACTERIUM MARITYPICUM - RACHNA BHATERIA; RAJESH DHANKHAR (International Journal of Pharma and Bio Sciences, 2013)
In the present study, a novel indigenous bacterium was isolated from the effluent of Electroplating industry having capability of biotransforming Cr(VI) ions into Cr(III) ions. Morphological, Physiological and biochemical characterization of the bacterial strain was carried out and later sequence analysis of 16S rRNA gene of the strain identified it as Microbacterium maritypicum. By utilizing this bacterial strain, Response surface methodology was used to study the interactive effect of three crucial operating parameters viz pH, temperature and initial Cr(VI) ion concentration on the process of Cr(VI) Biotransformation. Total seventeen experiments designed by Box-Behnken design matrix were carried out for the bacterial strain for the construction of quadratic model. Analysis of variance (ANOVA) was calculated. The coefficient of determination (R2) value 0.9509, model F- value 15.06 and its low P-value (F < 0.0009) ensured that second-order regression model got well fitted with the experimental data. The regression equation coefficients were also calculated. All the experimental observations were in agreement with the model values.